2010
DOI: 10.4269/ajtmh.2010.09-0431
|View full text |Cite
|
Sign up to set email alerts
|

Disinfection By-Product Formation and Mitigation Strategies in Point-of-Use Chlorination with Sodium Dichloroisocyanurate in Tanzania

Abstract: Abstract. Almost a billion persons lack access to improved drinking water, and diarrheal diseases cause an estimated 1.87 million deaths per year. Sodium dichloroisocyanurate (NaDCC) tablets are widely recommended for household water treatment to reduce diarrhea. Because NaDCC is directly added to untreated water sources, concerns have been raised about the potential health impact of disinfection by-products. This study investigated trihalomethane (THM) production in water from six sources used for drinking (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 19 publications
2
33
0
Order By: Relevance
“…On the other hand, much less is known about the effect of point‐of‐use disinfection on chemical water quality, for instance regarding the formation of undesirable disinfection by‐products (DBPs) (Lantagne et al . ; Smith et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, much less is known about the effect of point‐of‐use disinfection on chemical water quality, for instance regarding the formation of undesirable disinfection by‐products (DBPs) (Lantagne et al . ; Smith et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…THMs formation in point of use surface water disinfection is less well investigated (Lantagne et al . ; Smith et al . ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…TOC is used to quantify natural organic matter (NOM) which has been emphasized as the precursor to disinfection by-products including trihalomethanes (THMs) [38]. United States Environmental Protection Agency (USEPA) indicates that water with TOC above 2 mg/L requires treatment to avoid THMs formation [39] and in consequence this is a target value for this case study as chlorination is often performed in an uncontrolled manner in Tanzania [40]. In the European guideline for drinking water, TOC is related to the indicator parameters, and it should not show abnormal change.…”
Section: Drinking Water Guidelinesmentioning
confidence: 99%
“…The tablets are active over wide ranges of pH, turbidity, hardness, and pathogenic challenge. The chemical is resistant to sunlight damages, offers single use packaging and its low weight packaging approach make it easy for distribution [24]. Clasen and Edmondson [25] reported that the use of household water treatment methods such as aqua tabs reduces the burden of Diarrhea in the community.…”
Section: Effectiveness Of the Household Water Treatmentmentioning
confidence: 99%